(untitled) (Brazilian Journal of Oceanography, 2019)
Many microalgae are rich in lipid. Due to their low growth rates in the autotrophic culture, the best alternative is to cultivate cells under different conditions such as heterotrophic or mixotrophic, which results in the highest yield of biomass and lipid in the shortest duration. In this study, Dunaliela bardawil (UTEX 2538) green microalgae was cultivated under different culture conditions, autotrophic, heterotrophic and mixotrophic, and effects on cell concentration, lipid production and reactive oxygen species (ROS), total chlorophyll and beta-carotene concentrations were investigated. Due to very low cellular growth, this alga is not recommended for heterotrophic culture. In terms of mixotrophic conditions containing different concentrations of glucose or acetate, the highest cell growth and lipid production in 60mM glucose was similar to the control (autotrophic condition), while the concentrations of chlorophyll and beta-carotene decreased. However, at all concentrations of acetate, a slight increase in cell growth was achieved, while the lipid content decreased. Additionally, the concentrations of chlorophyll and beta-carotene increased. A positive correlation was observed between beta-carotene biosynthesis and lipid production, as well as levels of reactive species of oxygen and lipid production in the presence of glucose and acetate. This study showed that for D. bardawil the mixotrophic culture with 60mM glucose was the most suitable type of culture for increasing lipid content and cell growth rates in less time (one week).